Communication in Success Learning in School - Sukardi, Sukardi (Universitas Negeri Semarang, 2017)
Communication is an important part of human activity. Included in the learning process where teachers need students' understanding of what is delivered both science and good influence on their attitudes, behaviors, and ways of thinking.Unfortunately, that does not always work. There are many problems that occur in the field and in the communication process. Then there must be a chosen communication strategy to achieve students' understanding for the success of learning. All-way communication can be a solution to communication problems involving all students to interact with teachers as well as with their own. In addition, the selection of desired communication strategy with the character and the back.